How to Recruit and Hire Great Software Engineers Building a Crack Development Team - McCuller, Patrick; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
Want a great software development team? Look no further. How to Recruit and Hire Great Software Engineers: Building a Crack Development Team is a field guide and instruction manual for finding and hiring excellent engineers that fit your team, drive your success, and provide you with a competitive advantage. Focusing on proven methods, the book guides you through creating and tailoring a hiring process specific to your needs. You$1 (Bll learn to establish, implement, evaluate, and fine-tune a successful hiring process from beginning to end. Some studies show that really good programmers can be as much as 5 or even 10 times more productive than the rest. How do you find these rock star developers? Patrick McCuller, an experienced engineering and hiring manager, has made answering that question part of his life's work, and the result is this book. It covers sourcing talent, preparing for interviews, developing questions and exercises that reveal talent (or the lack thereof), handling common and uncommon situations, and onboarding your new hires. How to Recruit and Hire Great Software Engineers will make your hiring much more effective, providing a long-term edge for your projects. It will: Teach you everything you need to know to find and evaluate great software developers. Explain why and how you should consider candidates as customers, which makes offers easy to negotiate and close. Give you the methods to create and engineer an optimized process for your business from job description to onboarding and the hundreds of details in between. Provide analytical tools and metrics to help you improve the quality of your hires. This book will prove invaluable to new managers. But McCuller$1 (Bs deep thinking on the subject will also help veteran managers who understand the essential importance of finding just the right person to move projects forward. Put into practice, the hiring process this book prescribes will not just improve the success rate of your projects$1 (Bit$1 (Bll make your work life easier and lot more fun.s
Keywords: Computer science; Computer Science; Programming Techniques